Clinical and Refractive Outcomes of Toric Phakic Implantable Collamer lens Implantat for correction of myopic astigmatism - Amana, Suzan (AL-Kindy College Medical Journal, 2019)
Background: Currently there are four general approaches to correct refractive errors: refractive corneal surgery, crystalline lens surgery and implantation of an intraocular lens in anterior or posterior chamber. Objective: To evaluate the predictability, safety and stability of toric phakic implantable collamer lens implantation to correct moderate to high myopic astigmatism. in Eye Specialty Private Hospital, Baghdad, Iraq. Type of the Study: a prospective non randomize intervention study. Methods: 60 eyes of 40 patients underwent implantation of a toric implantable collamer lens (V4c design).Mean spherical refraction was ₋11.32 diopter (D) ±3.17 (SD) with range from ₋6.00 to ₋18.00D and the mean cylinder was -2.61(D) ±1.16 with range from ₋1.00 to ₋5.50D .The outcome measures that evaluated during a 12 months follow-up period include UDVA, refractive outcomes, CDVA, vault and adverse events. Results: At 12 months postoperatively the mean Snellen decimal UDVA was 0.77±0.23 and mean CDVA was 0.80±0.21, with an efficacy index 1.16. Twenty nine eyes (48.33%) showed gain in CDVA with safety index 1.21.The treatment was highly predictable for spherical equivalent and astigmatic component .The mean SE dropped from (₋12.63D ±3.11) to ( ₋0.11 D±0.20) with 58 eyes within ±0.50 D and 60 eyes with ± 1.00D of target correction . For achieved cylinder 60 eyes (100%) had ≤0.50D and 51 eyes (85%) had ≤0.25D with strong positive linear correlation between achieved and expected cylinder(r=0.94) Conclusions: The results of the present study support safety, efficacy, predictability of toric implantable collamer lens implantation to treat moderate to high myopic astigmatism.